LINGUISTIK FORENSIK: KONSEP DAN MODEL PENELITIAN (STUDI KASUS UNDANG-UNDANG NO. 21 TAHUN 2011 TENTANG OTSUS PAPUA) - Hugo Warami (Balai Bahasa Provinsi Papua, 2019)
This paper aims to reveal the nature of science that comes from forensic linguistics, namely the realm of interdisciplinary sciences of language, crime, and law. In it the law, including law enforcement, judicial matters, regulations, disputes or legal proceedings, and even disputes only potentially involve some violation of law or the need to seek some mode of legal remedy.The fact today illustrates that forensic linguistics has common characteristics that allow can be aligned into the practices of linguistic and discourse analytical others namely: (1) has a parameter forensic (legal and criminal) on linguistics, (2) as a surgical instrument used in hacking the relationship between language, law, and criminal, (3) a study of the language of the texts of laws, (4) media dismantle pragmatism legal language, (5) exposing the evil language, and (6) into a pillar of reconciliation between disputing parties law.Forensic linguistics can position the language, crime and law through interdisciplinary perspective as a vital part of human faced throughout his life. Paradigm evidentiary forensic linguistics implies granting absolute certainty for each person based on logic and observations obtained from the value sense and reasonableness. Forensic linguistics can be explored above, namely (1) the general characteristics, (2) the area of research, (3) the basic principle, (4) the mechanism of action, and (5) review the facts forensic linguistics.